A method for preparing a multifunctional material for extracting uranium from seawater
By performing halogenated rubber coating and functional treatment on the surface of fibers, fabrics or non-woven fabrics of seawater uranium extracting materials, multifunctional seawater uranium extracting materials, solving the adsorption capacity, selectivity and stability of existing materials Inadequately, it has achieved efficient, economical and environmentally friendly uranium extraction effect.
Patent Information
- Application Number
- CN202410947925.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-07-16
AI Technical Summary
The existing seawater uranium extraction materials have shortcomings in adsorption capacity, selectivity, stability and resistance to marine microbial adhesion, and it is difficult to meet the efficient, economical and environmentally friendly seawater uranium extraction needs.
Surface grafted amidoxime, quaternary ammonium cation, and amine are prepared by performing halogenated rubber coating and functionalization treatment on the surface of fibers, fabrics or nonwoven fabrics, including quaternary ammonium salting, quaternary ammonium cation and amines. Multifunctional seawater uranium extracting materials of carboxybetaine or sulfobetaine.
It realizes the material's high hydrophilicity, antibacteriality, anti-marine biological pollution and rapid and effective adsorption of uranyl ion, which improves the adsorption capacity and selectivity of the material, and enhances its stability and service life in seawater.
Smart Images

Figure BDA0004946242570000051 
Figure BDA0004946242570000052 
Figure BDA0004946242570000061
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a multifunctional material for extracting uranium from seawater, in particular to a multifunctional seawater uranium extraction material with amidoxime, quaternary ammonium cation, amine group, carboxybetaine or sulfobetaine grafted on the surface thereof, which can be used for enrichment and extraction and separation of uranium in seawater and belongs to the field of functional materials. Technical Background
[0002] Over the past half century, many developed countries with oceanic origin have conducted comprehensive research and development on the distribution of uranium in seawater, technology and methods for extracting uranium from seawater, materials required for extracting uranium from seawater, engineering, safety, environment and benefits of extracting uranium from seawater, and have made significant progress. The key to extracting uranium from seawater is the combination of the substrate and uranium-absorbing ligand of the seawater uranium extraction material. The substrate is required to be tough and durable; the ligand has high selectivity and large capacity for uranium adsorption; the preparation method of the seawater uranium extraction material is simple, the fixed use and recycling are convenient, the elution cycle is energy-saving and environmentally friendly, and the economic benefits are high. Theoretical research and experiments over the years have shown that the combination of "polymer silk fabric + chelated uranium-absorbing ligand" is the preferred design and preparation scheme for seawater uranium extraction materials. The earliest selected combination of "polymer silk fabric + chelated uranium-absorbing ligand" is directly the amidoximation of polyacrylonitrile fiber. However, the amidoximation of polyacrylonitrile fiber has several insurmountable defects. ① In order to improve the adsorption capacity of amidoximated polyacrylonitrile fiber, it is hoped that the cyano group on the surface of polyacrylonitrile fiber will be amidoximated as much as possible. However, the mechanical properties of excessively amidoximated polyacrylonitrile fiber are relatively poor. ② The amidoxim groups contained in amidoximated polyacrylonitrile fiber have small degrees of freedom in three-dimensional space. It is very difficult to form a stable geometric complex with uranyl cation or uranyl carbonate anion in a ratio of 2:1 or 4:1, and it is easily absorbed by Fe in seawater. 3+ 、Ni 2+ 、Zn 2+ , Cu 2+ or VO 2+ etc.; ③ The hydrophilicity of amidoxime-treated polyacrylonitrile fiber is not high, and the complex adsorption with uranyl ions in seawater is slow, and it takes about 30 to 50 days to reach saturated adsorption; ④ After amidoxime-treated polyacrylonitrile fiber is immersed in seawater, it is adhered or wrapped by marine microorganisms in a short time and loses the function of adsorbing uranyl ions.
[0003] In order to find seawater uranium extraction materials and production technology that meet the conditions of good adsorption selectivity for uranyl cations or uranyl carbonate anions, fast adsorption rate, large saturated adsorption capacity, high hydrophilicity, large specific surface area in contact with seawater, high mechanical strength, high chemical stability, resistance to adhesion of microorganisms in seawater, simple adsorption-desorption process, low recycling cost, durability, easy placement in open seawater, easy recovery and elution, and efficient operation, people have been working tirelessly. The research results of scholars from Japan, the United States, China and other countries have shown that the surface of fibers or non-woven fabrics based on polymer materials such as polyethylene, polypropylene or polystyrene grafted with functional monomers such as acrylonitrile and acrylic acid, itaconic acid, or vinylphosphonic acid is a satisfactory combination of "polymer silk fabric + chelating uranium adsorption ligand". First, synthetic polymer substrates such as polyethylene, polypropylene or polystyrene have large production, wide sources, low prices, high chemical stability, and surface grafting has almost no effect on their own mechanical properties; secondly, non-woven fabrics have high porosity and large specific surface area, and the processes of hot pressing, shearing, curling, folding, kneading, and weaving are simple, making them suitable for weaving nets, ropes, tree branches and leaves, kelp, or seaweed-like locations in the open ocean at various depths to absorb and filter seawater. In addition to grafting acrylonitrile for amidoximation, functional monomers containing ligands are also selected, including: ① acrylic acid, itaconic acid, unsaturated phosphoric acid / unsaturated phosphonic acid, unsaturated sulfobetaine, unsaturated phosphorylcholine, or unsaturated carboxybetaine for grafting copolymerization. These functional groups can enhance the selective complexation of amidoxime to uranyl cations or uranyl carbonate anions; ② unsaturated quaternary ammonium salts or unsaturated phosphorylcholines, which can not only significantly improve the surface hydrophilicity of these polymer materials and achieve wet contact between seawater and uranium extraction materials, but also attract uranyl carbonate anions to aggregate to the materials through the electrostatic attraction of their positive charges, thereby achieving aggregated and rapid ion exchange between the materials and seawater, and can also enhance the uranium extraction materials' resistance to the attachment and growth of marine microorganisms on their surfaces; ③ organic polyamines are grafted onto the surface of fibers or non-woven fabrics, which can improve the hydrophilicity and uranium absorption capacity of the materials. In view of this, how to design an all-round seawater uranium extraction material and a simple and effective preparation method based on existing research results should be the key to improving the comprehensive benefits of seawater uranium extraction today. Summary of the invention
[0004] More than ten years ago, the members of the research group of the present invention used fibers as substrates, impregnated and coated with polyacrylate, and then through the ring-opening reaction of organic polyamines and glycidyl groups, the quaternary ammonium quaternization reaction of 5-chloromethyl salicylaldehyde, and the oximation reaction of hydroxylamine hydrochloride, a series of chelated ion exchange fibers with side chain support quaternary ammonium cations, amidoximes, and salicylaldehyde oxime functional groups were prepared, which can be used as seawater uranium extraction materials with anti-marine biofouling properties, see CN102500432B, CN102505480B, CN102631954B, CN102516425B. However, in the application test, it was found that the series of chelated ion exchange fibers with side chain support quaternary ammonium cations, amidoximes, and salicylaldehyde oxime functional groups had poor durability of ion exchange function in simulated seawater, and the adsorption selectivity for heavy metal ions was not high. After investigation, it was found that the ester bonds in the structure of the series of chelated ion exchange fibers are constantly hydrolyzed in weakly alkaline seawater and lose the bonded functional groups, and the adsorption stability of heavy metal ions is not high; at the same time, the chelated ion exchange fiber has a high swelling rate when exposed to water. In recent years, the seawater uranium extraction materials that are highly praised are polyethylene or polypropylene fibers and their non-woven fabrics as the base material, and acrylonitrile and unsaturated functional monomers are grafted on the surface after ultraviolet irradiation, γ-irradiation or plasma. However, people have also found that the high-energy radiation grafting method without the use of chemical reagents is clean and environmentally friendly, and the improved process of grafting after pre-irradiation still does not completely solve the homopolymerization problem of acrylonitrile and unsaturated functional monomers; there is also m 2 The continuous production process of radiation grafting of large-area substrates is limited.
[0005] Amidoxime has always been considered to be the most effective chelating ligand for uranyl ions, so people's eyes have been fixed on grafting as much acrylonitrile or functional ligand as possible on the substrate surface (some reports have shown that the acrylonitrile grafting rate is as high as 500% or more), while ignoring the fixing effect of the substrate and the pulling effect of the polyacrylonitrile chain. As a result, the ortho-amidoxime converted by grafting acrylonitrile on the substrate surface has a small degree of freedom in the geometric space and is not suitable for 2:1 or 4:1 coordination and complexation with uranyl ions. Therefore, many results have reported that the utilization rate of amidoxime on the substrate surface for chelating and adsorbing uranyl ions is very low. The inventors believe that increasing the degree of freedom of the two adjacent amidoximes on the surface of the substrate is conducive to the "self-assembly" stable coordination complex of the amidoxime with the uranyl ion at a ratio of 2:1 or 4:1; at the same time, relying on the electrostatic attraction of the charges carried on the surface of the substrate to the uranyl ion, the substrate "casts a wide net" to actively collect extremely low concentration uranyl ions from the vast seawater on the surface of the substrate, thereby generating a "self-assembly" stable coordination complex of the amidoxime with the uranyl ion at a ratio of 2:1 or 4:1. So far, the inventors have created the preparation technology and scheme of the multifunctional material for "casting a wide net + self-assembly" for uranium extraction from seawater.
[0006] Based on the summary of existing work, the inventors have found through careful screening and experimental research that using halogenated rubber glue to coat the surface of the seawater uranium extraction substrate, and then quaternizing and functionalizing the halogenated rubber coating is a method for preparing a multifunctional material for seawater uranium extraction with a simple technical solution, wide adaptability of the substrate, continuous production process, and excellent functions and performance. The polymer chemistry principle of coating the substrate surface with halogenated rubber and then grafting functionalization of the multifunctional material for seawater uranium extraction described in the present invention is: ① The main chain and side chain of the outer layer of the halogenated rubber coating contain a large number of C=C double bonds, and these exposed C=C double bonds can be used as graft polymerization reaction centers initiated by oil-soluble free radical initiators; ② The C=C double bonds contained in the main chain and side chain of the inner layer of the halogenated rubber coating can be subjected to free radical vulcanization initiated by an oil-soluble free radical initiator, or bonded and cross-linked with the polymer chain of the substrate, thereby improving the mechanical strength of the rubber coating and strengthening its cross-linking and enhancing interface adhesion with the substrate. ③ The 3-bromo (or chloro) allyl unit in the halogenated rubber chain structure is easily subjected to quaternary ammonium salt reaction with N-(2-cyanoethyl)-N,N-diallylamine to obtain an unsaturated quaternary ammonium cationic rubber containing cyano groups on the surface; the unsaturated quaternary ammonium cationic rubber containing cyano groups on the surface can be subjected to a graft copolymerization reaction initiated by an aqueous free radical initiator with acrylonitrile, cyano-containing diallyl ammonium type ionic monomers, polycyano-containing bis (diallyl ammonium) crosslinking agents, etc. to obtain a rubber with cyano groups, polyquaternary ammonium cationic chains, or polybetaine grafted on the surface; and then subjected to an amidoximation reaction with hydroxylamine hydrochloride to obtain the multifunctional seawater uranium extraction material with amidoxime, amine, carboxy betaine, or sulfo betaine grafted on the surface. From the above simple principle introduction, professionals can already understand that the substrate of uranium extraction from seawater and materials should be coated with halogenated rubber, and then free radical-induced vulcanization, cross-linking, and copolymerization and grafting of multiple active centers should be carried out, which not only completes the free radical vulcanization of the unsaturated rubber in the coating and the strengthening of the bond and cross-linking with the substrate, but also introduces multifunctional hydrophilic, antibacterial, antifouling, and chelating groups such as amidoxime, quaternary ammonium cation, amine, carboxybetaine, or sulfobetaine on the surface of uranium extraction from seawater and materials.
[0007] The specific preparation scheme of the multifunctional material for extracting uranium from seawater with simple preparation method and excellent performance according to the present invention is described in detail as follows:
[0008] The halogenated rubber liquid refers to a halogenated rubber solution prepared by dissolving one or more of brominated natural rubber, brominated butyl rubber, brominated nitrile rubber, brominated polybutadiene, chlorinated natural rubber, chlorinated butyl nitrile rubber or chlorinated polybutadiene in a solvent, or a halogenated rubber emulsion prepared by dispersing one or more of brominated natural rubber, brominated butyl rubber, brominated nitrile rubber, brominated polybutadiene, chlorinated natural rubber, chlorinated butyl nitrile rubber or chlorinated polybutadiene in water.
[0009] The substrate refers to one or more of fiber, fabric or nonwoven fabric.
[0010] The fibers, fabrics or nonwoven fabrics mentioned herein refer to natural fibers with polysaccharides or proteins as basic raw materials, and fabrics or nonwoven fabrics processed from natural fibers as main raw materials; or synthetic fibers with synthetic materials as basic raw materials, and fabrics or nonwoven fabrics processed from synthetic fibers as main raw materials; or blended fibers, composite fibers, composite woven fabrics or nonwoven fabrics processed from natural fibers and synthetic fibers as main raw materials.
[0011] The synthetic material refers to one or more of polyethylene, polypropylene, polystyrene, polyvinylidene fluoride, polyvinyl chloride, polyester, polyacrylonitrile, polyurethane, polyamide, and polyvinyl acetal.
[0012] From the above technical scheme and substantial content of the present invention, professionals have realized that the present invention uses halogenated rubber glue to coat or glue the fiber, fabric or non-woven fabric on the surface, and its purpose is to uniformly coat the rubber coating on the surface of the fiber, fabric or non-woven fabric, wherein the 3-primary bromine (chlorine) allyl unit or 3-secondary bromine (chlorine) allyl unit contained in the outer layer of the rubber coating is easy to react with N-(2-cyanoethyl)-N,N-diallylamine to complete nucleophilic substitution reaction at room temperature, so as to realize unsaturated quaternary ammonium saltization on the surface of the rubber coating; the generated diallyl ammonium is the active site of the copolymerization grafting reaction, so that polyacrylonitrile or polyquaternary ammonium cation is grafted on the surface of the rubber coating, which is to establish the first grafting reaction center for preparing the multifunctional seawater uranium extraction material with surface bonded amidoxime, quaternary ammonium cation, amine, carboxybetaine, or sulfobetaine of the present invention;
[0013] The intrinsic C=C double bonds contained in the halogenated rubber coating also provide free radical crosslinking reaction centers for the preparation of the multifunctional seawater uranium extraction material of the present invention, and free radical vulcanization of the rubber chain is carried out to strengthen the mechanical properties of the rubber layer; in addition, free radical crosslinking of the rubber chain with the fiber, fabric or non-woven fabric can be initiated, and the strong polarity of the halogen atoms or cyanide groups in the rubber layer can be combined to enhance the bonding strength of the two interfaces between the rubber layer and the fiber, fabric or non-woven fabric, thereby providing a guarantee for the mechanical properties of the multifunctional seawater uranium extraction material of the present invention.
[0014] Further, under the condition of giving priority to the optimization performance requirements, the substrate surface can be subjected to coating pretreatment. The coating pretreatment of the substrate surface refers to coating pretreatment of the substrate surface with a polymer solution or a polymer emulsion, the purpose of which is to improve the interfacial bonding strength between the halogenated rubber coating and the substrate.
[0015] The polymer solution or polymer emulsion refers to one of halogenated rubber solution, resorcinol-formaldehyde condensation resin solution or emulsion, epoxy resin solution or emulsion, or polyvinyl alcohol-formaldehyde condensation resin solution or emulsion for coating pretreatment on the substrate surface.
[0016] The halogenated rubber solution used for coating pretreatment of the substrate surface refers to a halogenated rubber solution containing a fat-soluble initiator; the amount of the fat-soluble initiator in the halogenated rubber solution containing a fat-soluble initiator is 0.05-5% of the mass of the halogenated rubber in the halogenated rubber solution containing a fat-soluble initiator.
[0017] Before the coating pretreatment is performed on the surface of the fiber, fabric or nonwoven fabric based on polyethylene, polypropylene or polystyrene, the surface must be pre-activated. The surface pre-activation treatment refers to one of the following: acidic oxidation treatment with potassium permanganate aqueous solution, plasma radiation treatment in oxygen atmosphere, radiation treatment in air atmosphere, or corona discharge treatment. After the surface of the fiber, fabric or nonwoven fabric based on polyethylene, polypropylene or polystyrene is pre-activated, groups such as -OH, -CHO or -COOH are introduced to the surface, which improves the adhesion of the substrate surface, which is of great significance for ensuring the firmness of the substrate surface coated with halogenated rubber and then grafted with amidoxime, quaternary ammonium cation, amine group, carboxybetaine, or sulfobetaine.
[0018] The N-(2-cyanoethyl)-N,N-diallylamine is an unsaturated tertiary amine containing a cyano group, which undergoes a nucleophilic substitution reaction with the exposed 3-bromo(chloro)allyl structural unit of the halogenated rubber coating, and grafts unsaturated quaternary ammonium cations on the rubber coating. The unsaturated quaternary ammonium cation grafted on the rubber coating is a quaternary ammonium cation monomer, which participates in a graft copolymerization reaction initiated by an aqueous free radical initiator with acrylonitrile, a cyano-containing diallyl ammonium type ion monomer, a polycyano-containing bis(diallyl ammonium) crosslinking agent, etc., to achieve the first reaction center established for grafting amidoxime, amine, sulfobetaine, or carboxybetaine on the surface of the substrate. In order to satisfy the display of the second reaction center and to achieve free radical crosslinking between the rubber coating and the surface of the fiber, fabric or non-woven fabric, a fat-soluble initiator should be added to the halogenated rubber glue.
[0019] The cyano-containing diallyl ammonium type ion monomer has a structure shown in the general formula (I):
[0020]
[0021] Wherein Y in the general formula (I) is selected from substituted or unsubstituted C1-C 18 When the hydrocarbon group is - Select Cl- Br - or I - ;Y is -CH2CH2CO2 - 、-CH2CH2CH2CO2 - , or -CH2CH2CH2SO3 - When X - Do not select any kind of negative ions.
[0022] The polycyano-containing bis(diallylammonium) crosslinking agent has a structure shown in general formula (II):
[0023]
[0024] Among them, Select C1~C 18 Alkylene or X - Select Cl - Br - ,I - or p-CH3C6H4SO3 - One of , where n is selected from a natural number between 0 and 200.
[0025] Professionals are well aware that dimethyldiallylammonium chloride is a commonly used cationic monomer, and its homopolymer, copolymer and grafted polymer are widely used in water treatment, daily chemical industry, oil extraction and papermaking industry, etc. In order to create more diallylammonium chloride cationic monomers, people replace the dimethyl group with other hydrocarbon groups (such as butyl, hexyl, octyl, decyl, dodecyl, benzyl, etc.) or substituted hydrocarbon groups (carbonyl butoxyalkyl, etc.). The purpose is to meet different demand occasions and expand performance and functions; at the same time, the copolymerization of related diallylammonium chloride with allylamine hydrochloride, diallylamine hydrochloric acid, acrylamide, acrylic acid, methacryloyloxyethyl ammonium chloride, vinylbenzenesulfonic acid, vinyl phosphoric acid and other monomers has been clarified. To this end, based on the previous work of CN201110322472.5, CN201110322503.7, CN201110304602.2 and CN201110304603.7, the inventors, in accordance with the chemical principles of molecular design and based on the purpose and technical requirements of grafting acrylonitrile and functional monomers on the surface of seawater uranium extraction materials, disclosed in CN202311221445.8 cyano-containing diallylammonium type ionic monomers, cyano-containing diallylammonium type zwitterionic monomers, and polycyano-containing bis(diallylammonium) cross-linking agents, which are applied to the surface grafting modification of polymer materials to prepare multifunctional materials for seawater uranium extraction with excellent performance and comprehensive functions.
[0026] The specific preparation method of the multifunctional material for extracting uranium from seawater of the present invention comprises the following steps:
[0027] Step 1: Preparation of unsaturated quaternary ammonium cationized rubber latex
[0028] Weigh the solvent in a reactor at room temperature, add the halogenated rubber to the reactor under stirring, and raise the temperature of the materials in the reactor to 40-90°C until the halogenated rubber is completely dissolved to obtain a halogenated rubber solution; (the halogenated rubber solution obtained is cooled to room temperature, and a fat-soluble initiator is added thereto, and after being stirred and dissolved evenly, a halogenated rubber solution containing a fat-soluble initiator is obtained, which is set aside); after the halogenated rubber solution is nitrogen-filled and deoxygenated, N-(2-cyanoethyl)-N,N-diallylamine is added, and the reaction is kept warm for 12-20 hours, and the reaction is terminated and negative pressure concentration is performed to form a viscous fluid, and the concentration is stopped, and the temperature of the materials in the reactor is lowered to room temperature, and a fat-soluble initiator is added. After the fat-soluble initiator is dissolved, the materials in the reactor are continuously pumped into an aqueous solution containing a surfactant, and the emulsification process is completed by stirring to obtain an unsaturated quaternary ammonium cationic rubber emulsion containing a fat-soluble initiator, which is set aside. Reaction formula-1 schematically describes the preparation method of unsaturated quaternary ammonium cationic rubber using brominated rubber as an example:
[0029]
[0030] The mass ratio of the halogenated rubber / N-(2-cyanoethyl)-N,N-diallylamine / lipid-soluble initiator / solvent is 100:0.5-25:0.05-5:200-2000.
[0031] The halogenated rubber refers to one or more of brominated natural rubber, brominated butyl rubber, brominated nitrile rubber, brominated polybutadiene, chlorinated natural rubber, chlorinated nitrile rubber or chlorinated polybutadiene.
[0032] The fat-soluble initiator refers to one or more of benzoyl peroxide, cumene peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,4-bis(tert-butylperoxyisopropyl)benzene, lauroyl peroxide, azobisisobutyronitrile, azobisisoheptylnitrile or dioctyl azobisisobutyrate.
[0033] The solvent is selected from one or more of dichloromethane, chloroform, carbon tetrachloride, 1,2-dichloroethane, n-butanol, isobutanol, tert-butanol, tetrahydrofuran, 1,4-dioxane, 2-methoxyethanol, 2-ethoxyethanol, 2-ethoxyethanol acetate, ethyl acetate, methyl acetate, butyl acetate, toluene, xylene, acetone, butanone, cyclohexanone, chlorobenzene, cyclohexane, and petroleum ether.
[0034] The mass percentage of the surfactant in the aqueous solution is 0-5%, and the dosage of the aqueous solution is 0.5-2.5 times the mass of the halogenated rubber.
[0035] The surfactant is one or more of sodium stearate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether-10, octylphenol polyoxyethylene ether-10 or polyoxyethylene sorbitan monooleate.
[0036] Step 2: Preparation of surface-coated unsaturated quaternary ammonium cationic rubber coating substrate
[0037] At room temperature, the cleaned and surface-coated pretreated substrate is placed in the unsaturated quaternary ammonium cationized rubber emulsion containing a fat-soluble initiator prepared in step 1 for immersion or rolling, or the cleaned and surface-coated pretreated substrate surface is sprayed or roller-coated with the unsaturated quaternary ammonium cationized rubber emulsion containing a fat-soluble initiator prepared in step 1, and then the substrate evenly dipped or evenly coated with the unsaturated quaternary ammonium cationized rubber emulsion is sent to a dryer to obtain a substrate with a surface coated with an unsaturated quaternary ammonium cationized rubber coating.
[0038] The amount of the unsaturated quaternary ammonium cationic rubber latex used is 0.05 to 5 times the mass of the substrate.
[0039] The substrate refers to one of fiber, fabric or nonwoven fabric.
[0040] The fiber, fabric or non-woven fabric refers to a natural fiber with polysaccharide or protein as the basic raw material, and a fabric or non-woven fabric processed with natural fiber as the main raw material; or a synthetic fiber with synthetic material as the basic raw material, and a fabric or non-woven fabric processed with synthetic fiber as the main raw material; or a blended fiber, composite fiber, composite woven fabric or non-woven fabric processed with natural fiber and synthetic fiber as the main raw materials.
[0041] The synthetic material refers to one or more of polyethylene, polypropylene, polystyrene, polyvinylidene fluoride, polyvinyl chloride, polyester, polyacrylonitrile, polyurethane, polyamide, and polyvinyl acetal.
[0042] The surface coating pretreatment of the substrate refers to coating pretreatment of the substrate surface with a polymer solution or a polymer emulsion. The polymer solution or emulsion is selected from a halogenated rubber solution containing an oil-soluble initiator, a solution of resorcinol-formaldehyde condensation resin or an emulsion of resorcinol-formaldehyde condensation resin, a solution of epoxy resin or an emulsion of epoxy resin, or a solution of polyvinyl alcohol-formaldehyde condensation resin or an emulsion of polyvinyl alcohol-formaldehyde condensation resin;
[0043] The amount of the polymer solution or polymer liquid used is 0.05 to 5 times the mass of the substrate.
[0044] The halogenated rubber refers to one or more of brominated natural rubber, brominated butyl rubber, brominated nitrile rubber, brominated polybutadiene, chlorinated natural rubber, chlorinated nitrile rubber or chlorinated polybutadiene.
[0045] The fat-soluble initiator in the halogenated rubber solution containing the oil-soluble initiator is selected from one or more of benzoyl peroxide, isopropyl benzene peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,4-bis(tert-butylperoxyisopropyl)benzene, lauroyl peroxide, azobisisobutyronitrile, azobisisoheptylnitrile or dioctyl azobisisobutyrate; wherein the amount of the fat-soluble initiator in the halogenated rubber solution containing the oil-soluble initiator is 0.05-5% of the mass of the halogenated rubber.
[0046] The preparation method of the halogenated rubber solution containing an oil-soluble initiator is as follows: weigh the halogenated rubber solution, wait for the temperature of the halogenated rubber solution to drop to room temperature, add a fat-soluble initiator, stir and dissolve, and then obtain a halogenated rubber solution containing a fat-soluble initiator for use; wherein the amount of the fat-soluble initiator in the halogenated rubber solution containing a fat-soluble initiator is 0.05-5% of the mass of the halogenated rubber in the halogenated rubber solution.
[0047] Before the surface coating pretreatment is carried out on the fiber, fabric or non-woven fabric using polyethylene, polypropylene or polystyrene as the basic raw material, the surface is pre-activated.
[0048] The surface pre-activation treatment method is one of the following: acidic oxidation treatment with potassium permanganate aqueous solution, plasma radiation treatment in an oxygen atmosphere, γ-ray radiation treatment in an air atmosphere, or corona discharge treatment. Step 3: Preparation of a surface-grafted cyano-containing polyquaternary ammonium cationized substrate
[0049] The surface coated unsaturated quaternary ammonium cation rubber coating substrate obtained in step 2 is added to the graft copolymer solution, or the graft copolymer solution is sprayed on the surface of the substrate coated with the unsaturated quaternary ammonium cation rubber coating, or the graft copolymer solution is roller-coated on the surface of the substrate coated with the unsaturated quaternary ammonium cation rubber coating, and the substrate that has been evenly dipped or evenly coated with the graft copolymer solution is taken out and sent to a polymerization reactor, after nitrogen filling and deoxygenation for 30 minutes, the temperature is controlled at 50-60°C for oscillation polymerization reaction for 4-8 hours, and then the temperature is increased to 80-90°C for oscillation polymerization reaction for 2-4 hours, and the substrate is taken out from the polymerization reactor, and after cooling, washing, and drying, a surface grafted polyquaternary ammonium cationized substrate containing cyano groups is obtained. Formula-2 schematically expresses the structure of the surface grafted polyquaternary ammonium cationized substrate containing cyano groups:
[0050]
[0051] The graft copolymer solution is prepared by dissolving acrylonitrile / cyanide-containing diallyl ammonium type ionic monomer / polycyanide-containing bis(diallyl ammonium) crosslinking agent / aqueous initiator in deionized water in a mass ratio of 0-50:1-50:1-50:0.03-13:100; the amount of the graft copolymer solution used is 0.05-5 times the mass of the surface-coated rubber coating substrate.
[0052] The cyano-containing diallyl ammonium type ionic monomer has a structure shown in the general formula (I):
[0053]
[0054] Wherein Y in the general formula (I) is selected from substituted or unsubstituted C1-C 18 When the hydrocarbon group is - Select Cl - Br - or I - ;Y is -CH2CH2CO2 - 、-CH2CH2CH2CO2 - , or -CH2CH2CH2SO3 - When X - Do not select any kind of negative ions.
[0055] The polycyano-containing bis(diallylammonium) crosslinking agent has a structure shown in general formula (II):
[0056]
[0057] Among them, Select C1~C 18 Alkylene or X - Select Cl - Br - ,I - or p-CH3C6H4SO3 - One of , n is selected from a natural number between 0 and 200.
[0058] The aqueous initiator refers to one or more of hydrogen peroxide, sodium persulfate, potassium persulfate, ammonium persulfate, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid, or azobisisopropylimidazoline hydrochloride.
[0059] Step 4: Oximation reaction of surface grafted cyano-containing polyquaternary ammonium cationized substrate
[0060] Add hydroxylamine salt to deionized water, stir and dissolve, then use alkali to adjust the pH value to 6.0-8.5 to obtain a hydroxylamine aqueous solution, then immerse the surface-grafted polyquaternary ammonium cationized substrate containing cyanide obtained in step 3 into the hydroxylamine aqueous solution, control the temperature at 60-80°C, and oscillate the reaction for 10-12 hours. After cooling, take out the substrate, wash it, and centrifuge it to obtain the multifunctional material for extracting uranium from seawater of the present invention. Formula 3 schematically expresses the structure of the multifunctional material for extracting uranium from seawater:
[0061]
[0062] The hydroxylamine salt refers to hydroxylamine hydrochloride or hydroxylamine sulfate.
[0063] The alkali refers to one or more of sodium hydroxide, sodium carbonate, calcium oxide, or magnesium oxide.
[0064] The mass ratio of the surface-grafted cyano-containing polyquaternary ammonium cationized substrate / hydroxylamine salt / deionized water is 1:0.5-5:1-5:.
[0065] The beneficial effects of the multifunctional material for extracting uranium from seawater provided by the present invention are:
[0066] ① The technical solution of the present invention realizes the all-round and uniform grafting of a variety of functional ligands such as amidoxime, quaternary ammonium cation, tertiary amine, carboxybetaine or sulfobetaine on the surface of the substrate of the multifunctional material for extracting uranium from seawater. The key is that the grafting density can be artificially controlled.
[0067] ② The spacer arm of the amidoxime grafted on the surface of the multifunctional material for extracting uranium from seawater of the present invention is relatively long, and the amidoxime has a high degree of freedom in three-dimensional space, and can easily form a 2:1 or 4:1 geometric complex with uranyl ions or uranyl carbonate anions.
[0068] ③ The various functional ligands such as amidoxime, quaternary ammonium cation, tertiary amine, carboxybetaine or sulfobetaine on the surface of the multifunctional material for uranium extraction from seawater of the present invention have high stability in seawater or acid-base aqueous solution.
[0069] ④ The surface of the multifunctional material for extracting uranium from seawater of the present invention has high hydrophilicity, antibacterial property, anti-fouling by marine organisms, and zwitterion double exchange properties.
[0070] ⑤ The substrate and reagent raw materials required for preparing the multifunctional material for extracting uranium from seawater of the present invention are mostly industrial products, the raw materials are easy to obtain, the preparation method is simple, the cost is low, and the process is safe and efficient. DETAILED DESCRIPTION
[0071] The multifunctional material for extracting uranium from seawater and the preparation method thereof provided by the present invention are further described by the following examples, the purpose of which is to better understand the content of the present invention. Therefore, the multifunctional material for extracting uranium from seawater and the preparation method thereof not listed in the examples should not be regarded as limiting the scope of protection of the present invention.
[0072] Example 1 Preparation of multifunctional polyacrylonitrile fiber-1
[0073] Step 1: Preparation of unsaturated quaternary ammonium cationized rubber latex
[0074] Weigh 140 g of acetone and 60 g of tetrahydrofuran into a reactor, start stirring and add 18 g of brominated butyl rubber (BIIR2032, Beijing Yanshan Petrochemical Co., Ltd., bromine content of 2.36% by mass), control the temperature of the liquid in the reactor to 45-60°C, stir for 6 hours, and the brominated butyl rubber is dissolved to obtain a brominated butyl rubber solution; add a mixture of 10 g of isobutyl alcohol and 1.02 g of N-(2-cyanoethyl)-N,N-diallylamine to the brominated butyl rubber solution under N2 protection; The mixture was kept warm for 12 hours to terminate the reaction, and the low boiling point solvent was extracted under negative pressure. At this time, the liquid in the reactor was relatively viscous. The temperature of the material in the reactor was lowered to room temperature, and a mixture of 1.8 grams of azobisisoheptanenitrile and 6 grams of isobutanol was added. After stirring evenly, the material in the reactor was continuously poured into 40 grams of an aqueous solution containing 0.6 grams of polyoxyethylene sorbitan monooleate-10, and the emulsification process was completed by stirring to obtain 74 grams of brominated-N-(2-cyanoethyl)-N,N-diallyl ammonium rubber latex for standby use.
[0075] Take another 20 g of the brominated butyl rubber solution, wait for the temperature to drop to room temperature, add 0.82 g of azobisisobutyronitrile thereto, stir evenly, and obtain a brominated butyl rubber solution containing azobisisobutyronitrile for later use.
[0076] Step 2: Preparation of polyacrylonitrile fiber coated with unsaturated quaternary ammonium cationic rubber
[0077] At room temperature, 20 grams of cleaned and pre-activated polypropylene fiber is placed in the brominated butyl rubber solution containing azobisisobutyronitrile obtained in step 1 and rolled for 2 to 3 times, then the polyacrylonitrile fiber that has been evenly dipped in the brominated butyl rubber solution is taken out and sent to a dryer. After drying, 22.8 grams of polyacrylonitrile fiber pre-treated with brominated butyl rubber coating is obtained; 22.8 grams of polyacrylonitrile fiber with brominated butyl rubber coating on the surface is placed in the brominated-N-(2-cyanoethyl)-N,N-diallyl ammonium rubber emulsion obtained in step 1 and rolled for 2 to 3 times, then the polyacrylonitrile fiber that has been evenly dipped in the brominated-N-(2-cyanoethyl)-N,N-diallyl ammonium rubber emulsion is taken out, and after natural drying and curing, the surfactant, solvent, etc. are washed to remove, and then dried to obtain 26.6 grams of polyacrylonitrile fiber with unsaturated quaternary ammonium cationic rubber coating on the surface. Step 3: Preparation of surface-grafted polyionized polyacrylonitrile fiber-1 containing cyanide groups
[0078] Weigh 2.5 g of N-benzyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium chloride, 2.5 g of 4-(N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium)butyrate, 1 g of 1,4-bis(bromide N,N-diallyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)ammonium)butane and 0.55 g of azobisisobutylamidine hydrochloride, respectively, and dissolve them in 16 g of deionized water was added to obtain a graft copolymer solution; 26.6 g of the polyacrylonitrile fiber coated with an unsaturated quaternary ammonium cationic rubber coating obtained in step 2 was placed in the above graft copolymer solution for immersion 2 to 3 times, nitrogen was filled for deoxygenation for 0.5 hour, the temperature was raised to 50 to 60°C, oscillated polymerization was performed for 4 hours, the temperature was raised to 80 to 85°C, oscillated polymerization was performed for another 4 hours, the temperature was lowered, the fiber was extracted, the fiber was washed with water, and centrifuged at a constant speed of 2000±200 rpm for 5 minutes to obtain 58.2 g of surface-grafted polyionized polyacrylonitrile fiber-1 containing cyanide.
[0079] Thermogravimetric analysis revealed that the mass percentage of volatile matter in the 58.2 g surface-grafted cyanide-containing polyionized polyacrylonitrile fiber-1 was 45.73%, and the grafting rate was calculated to be ((58.2×0.5427-26.6)÷26.6)×100%=18.7%; wherein the grafting efficiency was (58.2×0.5427-26.6)÷6.55=76.1%.
[0080] Step 4: Preparation of multifunctional polyacrylonitrile fiber-1 for extracting uranium from seawater
[0081] Add 10 g of hydroxylamine hydrochloride to 30 mL of deionized water, adjust the pH value to 7.0-7.5 with a 20% mass percentage caustic soda aqueous solution, immerse 58.2 g of the surface-grafted cyanide-containing polyionized polyacrylonitrile fiber-1 obtained in step 3, control the temperature at 60-80° C., oscillate and react for 12 hours, take out the fiber after cooling, wash it with water until it is neutral, and centrifuge it at a constant speed of 2000±200 rpm for 5 minutes to obtain 67.7 g of multifunctional polyacrylonitrile fiber-1.
[0082] Thermogravimetric analysis shows that the volatile content of the multifunctional polyacrylonitrile fiber-1 is 45.18%, indicating that the actual weight of 67.7 grams of multifunctional polyacrylonitrile fiber-1 is 37.8 grams. At room temperature, it was immersed in artificial seawater containing uranyl nitrate. The test measured the saturated adsorption time of 7.5 minutes and the saturated adsorption capacity of 147.5 mg / g. The initial contact angle of pure water of the multifunctional polyacrylonitrile fiber-1 was 37.3°. After 20 seconds, the pure water droplet completely wetted the fiber, indicating that the pure water contact angle of the multifunctional polyacrylonitrile fiber-1 prepared by the present invention was significantly reduced compared with the original polyacrylonitrile fiber 1 of 112.5°.
[0083] Comparative Example 1 Preparation of Multifunctional Polyacrylonitrile Fiber-2
[0084] According to the method and steps of Example 1, the step 3 of Example 1, "respectively weigh 2.5 grams of N-benzyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium chloride, 2.5 grams of 4-(N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium)butyrate, 1 gram of 1,4-bis(bromide N,N-diallyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)ammonium)butane and 0.55 grams of azobisisobutylamidine hydrochloride, and dissolve them in 15 grams of deionized water to prepare a graft copolymer solution;" is replaced by "separately weigh 2.5 grams of N-benzyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium chloride, 2.5 grams of 4-(N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium)butyrate, 1 gram of 1,4-bis(bromide N,N-diallyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)ammonium)butane and 0.55 grams of azobisisobutylamidine hydrochloride, and dissolve them in 15 grams of deionized water to prepare a graft copolymer solution;" Separately weigh 1.5 g of N-benzyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium chloride, 1.5 g of 4-(N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium)butyrate, 3 g of 1,4-bis(bromide N,N-diallyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)ammonium)butane and 0.55 g of azobisisobutylamidine hydrochloride, dissolve them in 15 g of deionized water to prepare a graft copolymer solution; ", and prepare 45.7 g of surface-grafted cyano-containing polyionized polyacrylonitrile fiber-2. Thermogravimetric analysis revealed that the mass percentage of volatile matter in the 45.7 g surface-grafted cyanide-containing polyionized polyacrylonitrile fiber-2 was 35.68%, and the grafting rate was calculated to be ((45.7×0.6432-23.5)÷23.5)×100%=25.1%; wherein the grafting efficiency was (45.7×0.6432-23.5)÷6.55=90.7%.
[0085] The oximation reaction conditions of step 4 of Example 1 were adopted to carry out oximation reaction on the surface grafted polyionized polyacrylonitrile fiber-2 containing cyanide groups to obtain multifunctional polyacrylonitrile fiber-2. At room temperature, the saturated adsorption time of multifunctional polyacrylonitrile fiber-2 for uranyl ions was measured to be 7.5 minutes, and the saturated adsorption capacity was 153.9 mg / g. The initial contact angle of pure water of multifunctional polyacrylonitrile fiber-2 was measured to be 32.5°, and after 20 seconds, the pure water droplet completely infiltrated the fiber, indicating that the pure water contact angle of multifunctional polyacrylonitrile fiber-2 obtained by the method of the present invention was significantly reduced compared with the original polyacrylonitrile fiber 112.5°.
[0086] Comparative Example 2 Preparation of Multifunctional Polyacrylonitrile Fiber-3
[0087] According to the method and steps of Example 1, the step 3 of Example 1, "respectively weigh 2.5 g of N-benzyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium chloride, 2.5 g of 4-(N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium)butyrate, 1 g of 1,4-bis(bromide N,N-diallyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)ammonium)butane and 0.55 g of azobisisobutylamidine hydrochloride, and dissolve them in 15 g of deionized water to prepare a graft copolymer solution;" is replaced by "respectively weigh 2.5 g of N-benzyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium chloride, 2.5 g of 4-(N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium)butyrate, 1 g of 1,4-bis(bromide N,N-diallyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)ammonium)butane and 0.55 g of azobisisobutylamidine hydrochloride, and dissolve them in 15 g of deionized water to prepare a graft copolymer solution;" 1.0 g of N-dodecyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium chloride, 1.0 g of 3-(N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)-N,N-diallylammonium)propanesulfonate, 4 g of 1,4-bis((chlorinated N,N-diallyl-N-(2-hydroxy-3-(N,N-bis(2-cyanoethyl)amino)propyl)ammonium)methyl)benzene and 0.55 g of azobisisobutylamidine hydrochloride were dissolved in 15 g of deionized water to obtain a graft copolymer solution; "48.2 g of surface-grafted cyano-containing polyionized polyacrylonitrile fiber-3 was obtained. Thermogravimetric analysis revealed that the mass percentage of volatile matter in the 48.2 g of surface-grafted cyanide-containing polyionized polyacrylonitrile fiber-3 was 38.14%, and the grafting rate was calculated to be ((48.2×0.6186-23.5)÷23.5)×100%=26.9%; wherein the grafting efficiency was (48.2×0.6186-23.5)÷6.55=96.4%.
[0088] The oximation reaction conditions of step 4 of Example 1 were adopted to carry out oximation reaction on the surface grafted polyionized polyacrylonitrile fiber-3 containing cyanide groups, and multifunctional polyacrylonitrile fiber-3 was obtained. At room temperature, the saturated adsorption time of multifunctional polyacrylonitrile fiber-3 for uranyl ions was measured to be 10.2 minutes, and the saturated adsorption capacity was 168.2 mg / g. The initial contact angle of pure water of multifunctional polyacrylonitrile fiber-3 was measured to be 32.5°, and after 20 seconds, the pure water droplet completely infiltrated the fiber, indicating that the pure water contact angle of multifunctional polyacrylonitrile fiber-3 obtained by the method of the present invention was significantly reduced compared with the original polyacrylonitrile fiber 112.5°.
[0089] Compared with the results of Example 1, Comparative Examples 1 and 2 show that increasing the proportion of the crosslinking agent in the copolymerization grafting solution is beneficial to improving the grafting efficiency.
[0090] Example 2 Preparation of Multifunctional Polypropylene Nonwoven Fabric-1
[0091] According to the preparation method and operation steps of Example 1, the pre-activated polyacrylonitrile fiber in step 2 of Example 1 is replaced with a pre-activated polypropylene melt-blown nonwoven fabric to prepare a multifunctional polypropylene nonwoven fabric-1. The multifunctional polypropylene nonwoven fabric-1 is immersed in artificial seawater containing uranyl nitrate, and the saturated adsorption time is 10.3 minutes, the saturated adsorption capacity is 211.3 mg / g, and the initial contact angle of pure water is 33.6° at room temperature. After 20 seconds, the pure water droplet completely infiltrates the multifunctional polypropylene nonwoven fabric-1, indicating that the pure water contact angle of the multifunctional polypropylene nonwoven fabric-1 prepared by the method of the present invention is significantly reduced compared with the original polypropylene melt-blown nonwoven fabric of 122.4°.
[0092] Comparative Example 3 Preparation of Multifunctional Polypropylene Nonwoven Fabric-2
[0093] According to the preparation method and operation steps of Example 1, the polyacrylonitrile fiber pre-activated in step 2 of Example 1 is replaced with 15.8 g of polypropylene melt-blown nonwoven fabric, which is pre-activated by γ-ray irradiation in a dry air atmosphere and then immersed in the graft copolymerization solution of step 3 of Example 1 as soon as possible. Under N2 protection, the temperature is controlled at 80°C and oscillated for 6 hours. After cooling and washing with water, the fabric is centrifuged at a constant speed of 2000±200 rpm for 5 minutes to obtain 38.9 g of surface-grafted polyionized polypropylene nonwoven fabric-2 containing cyano groups.
[0094] Thermogravimetric analysis revealed that the volatile content of the 38.9 g surface-grafted polyionized polypropylene nonwoven fabric-2 containing cyano groups was 38.44% by mass, from which the grafting rate was calculated to be ((38.9×0.6156-20)÷20)×100%=19.7%; wherein the grafting efficiency was (38.9×0.6156-20)÷6.55=60.26%. This indicates that the surface of the nonwoven fabric can be modified by grafting polyions containing cyano groups after pre-irradiation, but the grafting rate and grafting efficiency did not produce a significant improvement effect.
[0095] The surface-grafted polyionized polypropylene nonwoven fabric-2 containing cyanide was immersed in the hydroxylamine aqueous solution of step 4 of Example 1, and after oximation reaction, water washing, and centrifugal drying at a constant speed of 2000±200 rpm for 5 minutes, 43.4 grams of multifunctional polypropylene nonwoven fabric-2 was obtained.
[0096] Thermogravimetric analysis shows that the volatile content of the multifunctional polypropylene nonwoven fabric-2 is 38.32%, indicating that the actual weight of 43.4 grams of multifunctional polypropylene nonwoven fabric-2 is 26.76 grams. At room temperature, it was immersed in artificial seawater containing uranyl nitrate. The test measured the saturated adsorption time of 2.3 hours and the saturated adsorption capacity of 115.8 mg / g. The initial contact angle of pure water of the multifunctional polypropylene nonwoven fabric-2 was measured to be 30.5°. After 25 seconds, the pure water droplet completely infiltrated the nonwoven fabric-2, indicating that the pure water contact angle of the multifunctional polypropylene nonwoven fabric-2 prepared by the method of the present invention is significantly reduced compared with the original polypropylene melt-blown nonwoven fabric of 122.4°.
[0097] Comparative Example 4 Preparation of Multifunctional Polypropylene Nonwoven Fabric-3
[0098] According to the preparation method and operation steps of Example 1, the pre-activated polyacrylonitrile fiber in step 2 of Example 1 was replaced with 15.5 grams of polypropylene non-woven fabric pre-activated by γ-ray irradiation for 10 minutes in a dry air atmosphere, and immersed in the graft copolymerization solution in Comparative Example 1 as soon as possible. Under N2 protection, the temperature was controlled at 80°C and oscillated for 6 hours. After cooling, washing with water, and centrifuging at a constant speed of 2000±200 rpm for 5 minutes, 41.8 grams of surface-grafted cyano-containing polyionized polypropylene non-woven fabric-3 was obtained.
[0099] Thermogravimetric analysis shows that the volatile content of the 41.8 g surface-grafted polyionized polypropylene nonwoven fabric-3 containing cyano groups is 38.61% by mass, and the grafting rate is calculated to be ((41.8×0.6139-20)÷20)×100%=28.3%; wherein the grafting efficiency is (40.1×0.6139-20)÷6.55=86.4%. This indicates that the method of grafting the polypropylene nonwoven fabric after pre-irradiation can significantly improve the grafting efficiency by increasing the mass ratio of the crosslinking agent in the graft copolymerization solution.
[0100] 41.8 g of the surface-grafted cyano-containing polyionized polypropylene nonwoven fabric-3 was immersed in the hydroxylamine aqueous solution of step 4 of Example 1, and after oximation reaction, water washing, and centrifugal drying at a constant speed of 2000±200 rpm for 5 minutes, 62.8 g of multifunctional polypropylene nonwoven fabric-3 was obtained.
[0101] Thermogravimetric analysis shows that the volatile content of the multifunctional polypropylene nonwoven fabric-3 is 54.66%, indicating that the actual weight of 62.8 grams of multifunctional polypropylene nonwoven fabric-3 is 28.49 grams. At room temperature, it was immersed in artificial seawater containing uranyl nitrate. The test measured the saturated adsorption time of 2.5 hours and the saturated adsorption capacity of 113.1 mg / g. The initial contact angle of pure water of the multifunctional polypropylene nonwoven fabric-3 was measured to be 31.3°. After 30 seconds, the pure water droplet completely infiltrated the nonwoven fabric-3, indicating that the pure water contact angle of the multifunctional polypropylene nonwoven fabric-3 prepared by the method of the present invention is significantly reduced compared with the original polypropylene melt-blown nonwoven fabric of 122.5°.
[0102] Example 3 Preparation of Multifunctional Cotton Gauze-1
[0103] According to the preparation method and operation steps of Example 1, the polyacrylonitrile fiber pre-activated in step 2 of Example 1 was replaced with 20.2 g of cotton absorbent gauze with a specification of 40×40 and a density of 50×50. After being impregnated with the brominated butyl rubber solution containing azobisisobutyronitrile in step 1 of Example 1, the unsaturated quaternary ammonium cationic butyl rubber emulsion containing azobisisoheptanenitrile, and the graft copolymerization solution in step 3 of Example 1, 76.7 g of surface-grafted cyanide-containing polyionized gauze-1 was obtained. Thermogravimetric analysis revealed that the mass percentage of volatile matter in the 76.7 g surface-grafted cyano-containing polyionized gauze-1 was 54.07%, from which the grafting rate was calculated to be ((81.7×0.4593-32.4)÷32.4)×100%=15.8%; wherein the grafting efficiency was (81.7×0.4593-32.4)÷6.55=78.2%.
[0104] The surface grafted cyanide-containing polyionized gauze-1 was immersed in the hydroxylamine aqueous solution in step 4 of Example 1 to complete the oximation reaction. After washing with water, it was centrifuged and dried at a constant speed of 2000±200 rpm for 5 minutes to obtain 96.1 g of multifunctional all-cotton absorbent gauze-1.
[0105] Thermogravimetric analysis shows that the volatile content of 96.1 g of multifunctional all-cotton absorbent gauze-1 is 60.37%, indicating that the actual mass of 96.1 g of multifunctional all-cotton absorbent gauze-1 is 38.1 g. At room temperature, the multifunctional all-cotton absorbent gauze-1 is immersed in artificial seawater containing uranyl nitrate, and the saturated adsorption time is 18.7 minutes and the saturated adsorption capacity is 193.6 mg / g. The initial contact angle of pure water of the multifunctional all-cotton absorbent gauze-1 is 25.5°, and the pure water droplet infiltrates the multifunctional all-cotton absorbent gauze-1 after contacting the cloth surface for 20 seconds, indicating that the multifunctional all-cotton absorbent gauze-1 prepared by the method of the present invention has strong hydrophilicity.
[0106] Example 4 Preparation of Multifunctional Cotton Gauze-2
[0107] According to the preparation method and operation steps of Example 1, the brominated butyl rubber in step 1 of Example 1 was replaced with brominated polybutadiene to prepare a brominated polybutadiene solution containing benzoyl peroxide and an unsaturated quaternary ammonium cationic polybutadiene emulsion containing azobisisoheptonitrile.
[0108] The polyacrylonitrile fiber pre-activated in step 2 was replaced with 25 grams of cotton absorbent gauze with a specification of 40×40 and a density of 50×50, and was treated by impregnation with a brominated polybutadiene solution containing benzoyl peroxide, an unsaturated quaternary ammonium cationic polybutadiene emulsion containing azobisisoheptonitrile, and the graft copolymerization solution in step 3 of embodiment 1 to obtain 85.1 grams of surface-grafted polyionized gauze-2 containing cyano groups. Thermogravimetric analysis showed that the mass percentage of volatile matter of the 87.1 grams of surface-grafted polyionized gauze-2 containing cyano groups was 54.22%, and the grafting rate was calculated to be ((85.1×0.4578-33.5)÷33.5)×100%=16.3%; wherein the grafting efficiency was (85.1×0.4578-33.5)÷6.55=83.3%.
[0109] The surface grafted cyanide-containing polyionized gauze-2 was immersed in the hydroxylamine aqueous solution in step 4 of Example 1 to complete the oximation reaction. After washing with water, it was centrifuged and dried at a constant speed of 2000±200 rpm for 5 minutes to obtain 101.7 g of multifunctional all-cotton absorbent gauze-2.
[0110] Thermogravimetric analysis shows that the volatile content of 101.7 g of multifunctional all-cotton absorbent gauze-2 is 60.37%, indicating that the actual mass of 101.7 g of multifunctional all-cotton absorbent gauze-2 is 40.3 g. At room temperature, the multifunctional all-cotton absorbent gauze-2 is immersed in artificial seawater containing uranyl nitrate, and the saturated adsorption time is 18.7 minutes and the saturated adsorption capacity is 113.8 mg / g. The initial contact angle of pure water of the multifunctional all-cotton absorbent gauze-2 is 24.1°, and the pure water droplet contacts the cloth surface for 20 seconds to infiltrate the multifunctional all-cotton absorbent gauze-2, indicating that the multifunctional all-cotton absorbent gauze-2 prepared by the method of the present invention has strong hydrophilicity.
Claims
1. A method for preparing a multifunctional material for extracting uranium from seawater, characterized in that This is accomplished using the following steps: Step 1: Preparation of unsaturated quaternary ammonium cationic rubber latex containing fat-soluble initiator and halogenated rubber solution containing fat-soluble initiator Weigh a solvent in a reactor at room temperature, add halogenated rubber to the reactor under stirring, raise the temperature of the material in the reactor by 40 to 90° C., until the halogenated rubber is completely dissolved to obtain a halogenated rubber solution, nitrogen is filled and deoxygenated in the halogenated rubber solution for 30 minutes, N-(2-cyanoethyl)-N,N-diallylamine is added, and the reaction is carried out for 12 to 20 hours to complete the quaternary ammonium salt reaction, the reaction is terminated and negative pressure concentration is performed to form a viscous fluid, the concentration is stopped, the temperature of the material in the reactor is lowered to room temperature, a fat-soluble initiator is added, and after the fat-soluble initiator is dissolved, the material in the reactor is continuously injected into an aqueous solution containing a surfactant, and the emulsification process is completed by stirring to obtain an unsaturated quaternary ammonium cationic rubber latex containing a fat-soluble initiator, which is set aside; The mass ratio of the halogenated rubber / N-(2-cyanoethyl)-N,N-diallylamine / lipid-soluble initiator / solvent is 100:0.5-25:0.05-5:200-2000; The mass percentage of the surfactant in the aqueous solution is 0 to 5% and does not include the 0 endpoint, and the amount of the aqueous solution is 0.5 to 2.5 times the mass of the halogenated rubber; Then, the halogenated rubber solution is taken, and after the temperature thereof drops to room temperature, a fat-soluble initiator is added, and after stirring and dissolving, a halogenated rubber solution containing a fat-soluble initiator is obtained, which is then used for later use; The amount of the fat-soluble initiator in the halogenated rubber solution containing the fat-soluble initiator is 0.05-5% of the mass of the halogenated rubber in the halogenated rubber solution containing the fat-soluble initiator; Step 2: Preparation of surface-coated unsaturated quaternary ammonium cationic rubber coating substrate At room temperature, the cleaned and surface-coated substrate is placed in the unsaturated quaternary ammonium cationized rubber emulsion containing a fat-soluble initiator prepared in step 1 for dipping or padding, or the cleaned and surface-coated substrate is sprayed or roll-coated with the unsaturated quaternary ammonium cationized rubber emulsion containing a fat-soluble initiator prepared in step 1 on its surface, and then the substrate evenly dipped or evenly coated with the unsaturated quaternary ammonium cationized rubber emulsion containing a fat-soluble initiator is sent to a dryer to obtain a substrate coated with an unsaturated quaternary ammonium cationized rubber coating; The amount of the unsaturated quaternary ammonium cationic rubber latex containing a fat-soluble initiator is 0.05 to 5 times the mass of the substrate; The substrate refers to one of fiber, fabric or nonwoven fabric; The fiber, fabric or non-woven fabric refers to one of natural fibers with polysaccharides or proteins as basic raw materials, and fabrics or non-woven fabrics processed with natural fibers as main raw materials; or synthetic fibers with synthetic materials as basic raw materials, and fabrics or non-woven fabrics processed with synthetic fibers as main raw materials; or blended fibers, composite fibers, composite woven fabrics or non-woven fabrics processed with natural fibers and synthetic fibers as main raw materials; The synthetic material refers to one or more of polyethylene, polypropylene, polystyrene, polyvinylidene fluoride, polyvinyl chloride, polyester, polyacrylonitrile, polyurethane, polyamide, and polyvinyl acetal; The coating pretreatment of the substrate surface refers to coating pretreatment of the substrate surface with a polymer solution or a polymer emulsion; the amount of the polymer solution or the polymer emulsion is 0.05 to 5 times the mass of the substrate; Before the surface coating pretreatment of the fiber, fabric or nonwoven fabric based on polyethylene, polypropylene or polystyrene is carried out, the surface is pre-activated; wherein the method of the surface pre-activation treatment refers to one of the acidic oxidation treatment method using potassium permanganate aqueous solution, plasma radiation treatment method in oxygen atmosphere, γ-ray radiation treatment method in air atmosphere, or corona discharge treatment method; Step 3: Preparation of surface grafted cyano-containing polyquaternary ammonium cationized substrate The surface coated unsaturated quaternary ammonium cation rubber coating substrate obtained in step 2 is added to the graft copolymer solution, or the graft copolymer solution is sprayed or rolled on the surface of the surface coated unsaturated quaternary ammonium cation rubber coating substrate, and the substrate that has been evenly dipped or evenly coated with the graft copolymer solution is taken out and sent into a polymerization reactor, after nitrogen filling and deoxygenation for 30 minutes, the temperature is controlled at 50-60° C. and the polymerization reaction is carried out for 4-8 hours, and then the temperature is increased to 80-90° C. and the polymerization reaction is carried out for 2-4 hours, and the substrate is taken out from the polymerization reactor, and the temperature is lowered, washed, and centrifuged to obtain a surface grafted cyano-containing polyquaternary ammonium cationized substrate; The graft copolymer solution is prepared by dissolving acrylonitrile, a cyano-containing diallyl ammonium type ionic monomer, a polycyano-containing bis(diallyl ammonium) crosslinking agent, and an aqueous initiator in deionized water in a mass ratio of 0 to 50:1 to 50:1 to 50:0.03 to 13:100, which does not include the zero end point; the amount of the graft copolymer solution is 0.05 to 5 times the mass of the surface-coated rubber coating substrate; The cyano-containing diallyl ammonium type ionic monomer has a structure shown in the general formula (I): Wherein Y in the general formula (I) is selected from substituted or unsubstituted C1-C 18 When the hydrocarbon group is - Select Cl - Br - or I - ;Y is -CH2CH2CO2 - 、-CH2CH2CH2CO2 - , or -CH2CH2CH2SO3 - When X - Do not select any kind of negative ions; The polycyano-containing bis(diallylammonium) crosslinking agent has a structure shown in general formula (II): Among them, Select C1~C 18 Alkylene or X - Select Cl - Br - ,I - or p-CH3C6H4SO3 - One of, n is selected from a natural number between 0 and 200; Step 4: Preparation of multifunctional materials for uranium extraction from seawater Add hydroxylamine salt to deionized water, stir and dissolve, then use an appropriate amount of alkali to adjust the pH value to 6.0-8.5 to obtain a hydroxylamine aqueous solution, then immerse the surface-grafted cyano-containing polyquaternary ammonium cationized substrate obtained in step 3 into the hydroxylamine aqueous solution, control the temperature at 60-80° C., oscillate and react for 10-12 hours, take out the substrate after cooling, wash it with water, and centrifuge and dry it to obtain the multifunctional material for extracting uranium from seawater; The mass ratio of the surface-grafted cyano-containing polyquaternary ammonium cationized substrate / hydroxylamine salt / deionized water is 1:0.2-5:1-15.
2. A method for preparing a multifunctional material for extracting uranium from seawater according to claim 1, characterized in that The halogenated rubber refers to one or more of brominated natural rubber, brominated butyl rubber, brominated nitrile rubber, brominated polybutadiene, chlorinated natural rubber, chlorinated butyl rubber, or chlorinated polybutadiene.
3. A method for preparing a multifunctional material for extracting uranium from seawater according to claim 1, characterized in that The polymer solution or polymer emulsion refers to one of a halogenated rubber solution containing a fat-soluble initiator, a solution or emulsion of a resorcinol-formaldehyde condensation resin, a solution or emulsion of an epoxy resin, or a solution or emulsion of a polyvinyl formal resin; The amount of the polymer solution or polymer emulsion used is 0.05 to 5 times the mass of the fiber, fabric or non-woven fabric.
4. A method for preparing a multifunctional material for extracting uranium from seawater according to claim 1 or 3, characterized in that The fat-soluble initiator refers to one or more of benzoyl peroxide, cumene peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,4-bis(tert-butylperoxyisopropyl)benzene, lauroyl peroxide, azobisisobutyronitrile, azobisisoheptylnitrile or dioctyl azobisisobutyrate.
5. The method for preparing a multifunctional material for extracting uranium from seawater according to claim 1, characterized in that The solvent is selected from one or more of dichloromethane, chloroform, carbon tetrachloride, 1,2-dichloroethane, n-butanol, isobutanol, tert-butanol, tetrahydrofuran, 1,4-dioxane, 2-methoxyethanol, 2-ethoxyethanol, 2-ethoxyethanol acetate, ethyl acetate, methyl acetate, butyl acetate, toluene, xylene, acetone, butanone, cyclohexanone, chlorobenzene, cyclohexane, and petroleum ether.
6. A method for preparing a multifunctional material for extracting uranium from seawater according to claim 1, characterized in that The surfactant refers to one or more of sodium stearate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether-10, octylphenol polyoxyethylene ether-10 or polyoxyethylene sorbitan monooleate.
7. A method for preparing a multifunctional material for extracting uranium from seawater according to claim 1, characterized in that The aqueous initiator refers to one or more of hydrogen peroxide, sodium persulfate, potassium persulfate, ammonium persulfate, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid, or azobisisopropylimidazoline hydrochloride.
8. A method for preparing a multifunctional material for extracting uranium from seawater according to claim 1, characterized in that The hydroxylamine salt refers to hydroxylamine hydrochloride or hydroxylamine sulfate.
9. A method for preparing a multifunctional material for extracting uranium from seawater according to claim 1, characterized in that The alkali refers to one or more of sodium hydroxide, sodium carbonate, calcium oxide, or magnesium oxide.
Citation Information
Patent Citations
Super chelating ion exchange fiber
CN102500432A
Super chelating ion exchange fiber
CN102500432B
Super chelating ion exchange resin
CN102504061A
Preparation method of super chelating ion exchange fibers
CN102505480A
Preparation method of super chelating ion exchange fibers
CN102505480B